THE LIVED EXPERIENCES OF STRESS MANAGEMENT THROUGH CALLIGRAPHY ART THERAPY: A PHENOMENOLOGICAL APPROACH - Safina Fina; Masykur Arif; Rozinah AS. (Living Sufism: Journal of Sufism and Psychotherapy, 2026)
Stress is the inability of individuals to cope with stressful conditions in their environment. Each individual has different ways of dealing with it, one of which is through art therapy. This method is a therapeutic practice often used by several members of the PP. Annuqayah Lubangsa Putri Calligraphy Institute. In addition to being a routine activity, several members report that calligraphy has therapeutic benefits in reducing stress levels. This study aims to explore two aspects: first, how members of the Calligraphy Institute experience stress, including both stressors and stress symptoms; and second, the significance of calligraphy as art therapy for members of the Calligraphy Institute who experience stress. The researcher employs a phenomenological method, incorporating two theories—Farid Mashudi’s stressor theory and Sarafino’s stress symptom theory—as well as Malchiodi’s art therapy perspective theory, to uncover the therapeutic significance of calligraphy art for members of the Calligraphy Institute. This study concludes that there are three types of stressors experienced by members of the Calligraphy Institute, namely: psychological stressors such as negative thinking and frustration; biological stressors such as dissatisfaction with body shape; and social stressors such as social conflicts and a busy schedule. The identified symptoms encompass both psychological and biological aspects. Psychological symptoms include difficulty concentrating and reduced focus, while biological symptoms include headaches, eating disorders, and digestive problems. Furthermore, the informants conveyed several meanings of calligraphy art, including: calligraphy as a medium of expression and communication; a source of meditation and relaxation; a means to enhance self-understanding; a way to create personal- al satisfaction; a contributor to psychological well-being; and a support for strengthening spiritual aspects.